2020
DOI: 10.3390/cancers12071795
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Depletion of Subcutaneous Adipose Tissue during Sorafenib Treatment Predicts Poor Survival in Patients with Hepatocellular Carcinoma

Abstract: The aim of this study was to assess the annualized changes in body composition, including skeletal muscle, subcutaneous adipose tissue (SAT), and visceral adipose tissue (VAT) before, during, and after sorafenib treatment in patients with hepatocellular carcinoma (HCC). This retrospective study evaluated 61 HCC patients treated with sorafenib. Annualized changes (Δ; cm2/m2/year) in skeletal muscle index (SMI), SAT index (SATI), and VAT index (VATI), which were defined as the cross-sectional areas (cm2)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 35 publications
1
15
0
Order By: Relevance
“…18 records didn't meet the inclusion criteria and were discarded: 2 involving other kinase inhibitors (Nault et al, 2013[ 28 ], 2015[ 29 ]), 9 with overlapped patient data (Antonelli et al, 2018[ 2 ]; Gigante et al, 2015[ 13 ]; Hoshino et al, 2015[ 16 ]; Imai et al, 2015[ 17 ], 2019[ 19 ]; Labeur et al, 2018[ 23 ][ 24 ]; Okada et al, 2019[ 33 ]; Saeki et al, 2019[ 34 ]), 5 lacking HR and 95 % CI (Mir et al, 2012[ 26 ]; Okada et al, 2020[ 32 ]; Saeki et al, 2018[ 35 ]; Uchikawa et al, 2020[ 39 ]; Ueki et al, 2016[ 40 ]), 1 without any interesting outcome (Cheng et al, 2019[ 7 ]) and 1 with low quality and faulty data (Nishikawa et al, 2017[ 30 ]). Thus, 11 retrospective studies (Antonelli et al, 2018[ 3 ]; Endo et al, 2020[ 10 ]; Hiraoka et al, 2017[ 15 ]; Imai et al, 2020[ 18 ]; Labeur et al, 2019[ 25 ]; Naganuma et al, 2017[ 27 ]; Sawada et al, 2019[ 36 ]; Takada et al, 2018[ 38 ]; Uojima et al, 2020[ 41 ]; Wu et al, 2021[ 43 ]; Yamashima et al, 2017[ 45 ]) were included in this meta-analysis, comprising 1148 patients. The flow diagram of this study selection process is shown in Figure 1 (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…18 records didn't meet the inclusion criteria and were discarded: 2 involving other kinase inhibitors (Nault et al, 2013[ 28 ], 2015[ 29 ]), 9 with overlapped patient data (Antonelli et al, 2018[ 2 ]; Gigante et al, 2015[ 13 ]; Hoshino et al, 2015[ 16 ]; Imai et al, 2015[ 17 ], 2019[ 19 ]; Labeur et al, 2018[ 23 ][ 24 ]; Okada et al, 2019[ 33 ]; Saeki et al, 2019[ 34 ]), 5 lacking HR and 95 % CI (Mir et al, 2012[ 26 ]; Okada et al, 2020[ 32 ]; Saeki et al, 2018[ 35 ]; Uchikawa et al, 2020[ 39 ]; Ueki et al, 2016[ 40 ]), 1 without any interesting outcome (Cheng et al, 2019[ 7 ]) and 1 with low quality and faulty data (Nishikawa et al, 2017[ 30 ]). Thus, 11 retrospective studies (Antonelli et al, 2018[ 3 ]; Endo et al, 2020[ 10 ]; Hiraoka et al, 2017[ 15 ]; Imai et al, 2020[ 18 ]; Labeur et al, 2019[ 25 ]; Naganuma et al, 2017[ 27 ]; Sawada et al, 2019[ 36 ]; Takada et al, 2018[ 38 ]; Uojima et al, 2020[ 41 ]; Wu et al, 2021[ 43 ]; Yamashima et al, 2017[ 45 ]) were included in this meta-analysis, comprising 1148 patients. The flow diagram of this study selection process is shown in Figure 1 (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The main results of the crude and adjusted pooled analysis are reported in Figure 2A and 2B (Fig. 2) (References in Figure 2: Antonelli et al, 2018[ 3 ]; Endo et al, 2020[ 10 ]; Hiraoka et al, 2017[ 15 ]; Imai et al, 2020[ 18 ]; Labeur et al, 2019[ 25 ]; Naganuma et al, 2017[ 27 ]; Sawada et al, 2019[ 36 ]; Takada et al, 2018[ 38 ]; Uojima et al, 2020[ 41 ]; Wu et al, 2020[ 43 ]; Yamashima et al, 2017[ 45 ]) respectively. Ten studies involving 1028 patients provided the crude HRs and 95 % CIs of the association between the LSMM and HCC patients treated with sorafenib or lenvatinib (Antonelli et al, 2018[ 3 ]; Endo et al, 2020[ 10 ]; Hiraoka et al, 2017[ 15 ]; Imai et al, 2020[ 18 ]; Labeur et al, 2019[ 25 ]; Naganuma et al, 2017[ 27 ]; Sawada et al, 2019[ 36 ]; Takada et al, 2018[ 38 ]; Uojima et al, 2020[ 41 ]; Yamashima et al, 2017[ 45 ]).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, the prognostic impact of changes in body composition caused by sorafenib has been reported. Previous retrospective studies reported that the rapid depletion of skeletal muscle mass or subcutaneous adipose tissue was a poor prognostic factor for u-HCC patients treated with sorafenib [ 26 , 27 ]. In the present study, we evaluated the skeletal muscle condition only at the start of lenvatinib, so a further study is needed to confirm the prognostic impact of the changes in the body composition, including adipose tissue and muscle, in u-HCC patients treated with lenvatinib.…”
Section: Discussionmentioning
confidence: 99%